Ion pairing in 1-butyl-3-methylpyridinium halide ionic liquids studied using NMR and DFT calculations - Swamy, Vincent P.; Thulasiram, Hirekodathakallu V.; Rastrelli, Federico; Saielli, Giacomo (Physical Chemistry Chemical Physics, 2018)
We present the H-1, C-13 and N-15 NMR chemical shifts of bulk ionic liquids based on 1-butyl-3-methylimidazolium (the cation also known as 1-butyl-3-picolinium) halides (Cl-, Br- and I-) and tribromide (Br-3(-)) salts. A characterization in solution of the analogous ICl2- and I-3(-) salts is also reported. A series of DFT calculations has been run to predict the features of the NMR spectra of the pure ILs based on a few selected supramolecular ionic aggregates. To test the effect of temperature, and vibrational and conformational motions, only for the chloride salt, we also run first-principles molecular dynamics simulations of the ion pair in the gas phase, using the ADMP scheme (Atom Centered Density Matrix Propagation molecular dynamics model). The aim of our investigation is to test whether a simple DFT based approach of ion-pairing in ionic liquids is capable of providing reliable results and under which conditions the protocol is robust. We obtained a very good agreement between the calculated and experimental spectra for the three halides, where the bulk structure of the ILs is dominated by H-bond interactions between the X- anion (X = Cl, Br and I) and the ortho protons of the pyridinium ring (a structural arrangement not too different from the solid-state structure of pyridinium halides). In contrast, when the H-bond is weak, as in the Br-3(-) case, a number of supramolecular arrangements exist in solution and the simple DFT calculations of a few selected cases cannot exhaustively explore the complete energy landscape. Moreover, the dynamic effects due to thermal motion, evaluated by ADMP MD simulations of the chloride salt, appear to be not very significant.